Acoustic differentiation and behavioral response reveals cryptic species within Buergeria treefrogs (Anura, Rhacophoridae) from Taiwan. - Ying-Han Wang; Yu-Wei Hsiao; Ko-Huan Lee; Hui-Yun Tseng; Yen-Po Lin; Shohei Komaki; Si-Min Lin (PLoS ONE, 2017)
Buergeria japonica is a widely distributed treefrog occurring from Ryukyu Archipelago to Taiwan. Across this wide distributional range, we combined molecular, acoustic, morphological, and behavioral characters to clarify the taxonomic status among these insular populations. Genetic differentiation in mitochondrial sequences indicated an over 16% divergence among two deeply divergent clades: Japanese clade distributes in Ryukyu Archipelago and northwestern drainages of Taiwan, while Taiwanese clade distributes in the remaining drainages on Taiwan. The Taiwanese clade can be distinguished from the nominative species not only by molecular and morphological differences, but also distinguishable by considerable acoustic differentiation, which is extraordinarily noticeable for an additional type of long call that never recorded from Japanese clade. The two clades form a parapatric distribution pattern with narrow contact zones both in western and eastern Taiwan. Playback experiments indicated that male frogs show significantly stronger defensiveness against conspecific calls rather than heterospecific calls, indicating that these signals play a crucial role in species recognition. Here we describe the Taiwanese clade as a new species; the behavioral response and the magnitude of gene flow across their contact zones are especially worth for detailed studies.